The Use Of Symbols To Show The Main Character’s Personality In The Venom: Let there be carnage - Ramadhan, Novrian Dwi; Monika, Rike; Anggraini, Melia; Sembiring, Lina Tri Astuty Beru (Jurnal Ilmiah Wahana Pendidikan, 2024)
This article explores the role of linguistics and language in shaping thought, behavior, and personality. Drawing on the theories of Ferdinand de Saussure and Benjamin Lee Whorf, the study examines how linguistic categories and structures influence cognitive categorization, impacting individual perceptions of the world. Linguistics encompasses various fields, including phonology, phonetics, morphology, syntax, semantics, pragmatics, and language acquisition, all of which contribute to the understanding and analysis of language. The research employs the branch of pragmatics to analyze linguistic symbols found in the movie Venom: Let There Be Carnage, exploring how these symbols convey meaning and influence communication. The Sapir-Whorf hypothesis is also discussed, highlighting the notion that language can shape one's thoughts and worldview. Additionally, the article examines the relationship between language and personality, emphasizing the potential impact of linguistic structures on behavior and the development of mental health disorders. The study ultimately underscores the significance of language as a powerful tool that mediates between thought and sound, shaping human communication, perception, and identity. The chosen movie serves as a rich source of linguistic analysis, offering insights into the personality of the main character, Eddie Brock, through the use of language.